2008
DOI: 10.1111/j.1601-0825.2007.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Unstimulated whole saliva flow rate in relation to sicca symptoms in Hungary

Abstract: This cross sectional study, representative of the Hungarian population, clearly shows that one-third of the adult population suffers from xerostomia. The clinical severity of the xerostomia demonstrated a strong relationship with the lower levels of UWS flow rate. Reduced levels of UWS flow rate in this study were also shown to be associated with dysphagia, fatigue, and increased DMF-T numbers. The data show that oral dryness, its associated desiccation symptoms and its clinical manifestations are significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 29 publications
(47 reference statements)
2
41
1
4
Order By: Relevance
“…Although several studies have examined the relation between salivary flow and periodontal disease, a few reports have suggested that individuals with lower salivary flow rates have higher risks for periodontal disease (8,9,11). The present participants with a salivary flow rate ≤1.4 mL/min had a higher risk for extensive periodontal disease.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Although several studies have examined the relation between salivary flow and periodontal disease, a few reports have suggested that individuals with lower salivary flow rates have higher risks for periodontal disease (8,9,11). The present participants with a salivary flow rate ≤1.4 mL/min had a higher risk for extensive periodontal disease.…”
Section: Discussionmentioning
confidence: 48%
“…Yoshihiro Shimazaki 1,2) , Bohan Fu 1) , Koji Yonemoto 3,4) , Sumio Akifusa 1,5) , Yukie Shibata 1) , Toru Takeshita 1) , Toshiharu Ninomiya 6) , Yutaka Kiyohara 3) , and Yoshihisa Yamashita 1) decline in saliva secretion increased the risk of dental caries (7)(8)(9)(10). However, the extent to which caries risk increases because of decreased saliva production is unclear.…”
Section: Stimulated Salivary Flow Rate and Oral Health Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agrees with a previous study, where it was suggested that it might be that the overall dehydration associated with hyperglycemia decreased the volume of saliva excreted (Karjalainen et al, 1996). Low salivary flow can influence increased caries experience in DM patients (Siudikiene et al, 2006, Márton et al, 2008. Furthermore, the subjective feeling of dry mouth (xerostomia) may result from a reduction in saliva secretion and was shown to have a negative impact on the quality of life of adolescents with DM1 (Busato et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated a higher gingival bleeding and plaque index in subjects with hyposalivation but without shown a correlation between salivary flow rate and gingival bleeding index or plaque index (73,74).…”
Section: Periodontal Statusmentioning
confidence: 99%